GENDER AND SUSTAINABILITY IN THE ECONOMIC DEVELOPMENT - EQUAL CHANCES FOR WOMEN AT THE LABOUR MARKET - Sawicka, Janina; Łagoda, Joanna (Acta Scientiarum Polonorum. Oeconomia, 2015)
The article contains basic concepts of equal opportunity policy and gender issues. The economic dimension of equality policies were disused and evaluated. Assessment was done of the situation of women at national and European labour market. The reasons for lower participation and employment of women as well as their discrimination on the labour market were discussed. Statistical studies confirm that both in Poland and in European Union countries there are important differences in wages. Comparison of such measures as GII, GEI and GPG shows a clear division between groups of countries: the developed ones (mainly Scandinavian) where differences by gender are not present or are minor, group of countries from the Mediterranean basin, where situation of women is more sensitive to the influence of stereotypes and traditional patterns, and a less developed countries from Central and Eastern Europe, where women still do not have equal opportunities in the labour market.